2013
DOI: 10.1051/0004-6361/201220349
|View full text |Cite
|
Sign up to set email alerts
|

The extremely low-metallicity tail of the Sculptor dwarf spheroidal galaxy

Abstract: We present abundances for seven stars in the (extremely) low-metallicity tail of the Sculptor dwarf spheroidal galaxy, from spectra taken with X-shooter on the ESO VLT. Targets were selected from the Ca II triplet (CaT) survey of the dwarf abundances and radial velocities team (DART) using the latest calibration. Of the seven extremely metal-poor candidates, five stars are confirmed to be extremely metal-poor (i.e., [Fe/H] < −3 dex), with [Fe/H] = -3.47 ± 0.07 for our most metal-poor star. All have [Fe/H] ≤ −2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
134
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(144 citation statements)
references
References 86 publications
8
134
2
Order By: Relevance
“…below −2.5) that are known in Local Group Galaxies, and many are below −3.0. To date, the most metal-poor star known in external galaxies is found in Sculptor and has a metallicity near −4.0 (Tafelmeyer et al 2010); two more stars of similar metallicity are known in Sculptor (Frebel et al 2010a;Simon et al 2015) and six more below −3.0 (Starkenburg et al 2013;Simon et al 2015). Other local galaxies with at least one such star are Draco (Shetrone et al 2001;Fulbright et al 2004;Cohen & Huang 2009), Sagittarius (Zaggia et al 2004;Bonifacio et al 2006;Sbordone et al 2015;and Monaco et al, in prep.…”
Section: Low Scatter In the Iron-to-calcium Ratiomentioning
confidence: 99%
“…below −2.5) that are known in Local Group Galaxies, and many are below −3.0. To date, the most metal-poor star known in external galaxies is found in Sculptor and has a metallicity near −4.0 (Tafelmeyer et al 2010); two more stars of similar metallicity are known in Sculptor (Frebel et al 2010a;Simon et al 2015) and six more below −3.0 (Starkenburg et al 2013;Simon et al 2015). Other local galaxies with at least one such star are Draco (Shetrone et al 2001;Fulbright et al 2004;Cohen & Huang 2009), Sagittarius (Zaggia et al 2004;Bonifacio et al 2006;Sbordone et al 2015;and Monaco et al, in prep.…”
Section: Low Scatter In the Iron-to-calcium Ratiomentioning
confidence: 99%
“…Data for the observed stars to compare our simulation results with are taken from the SAGA (Stellar Abundances for Galactic Archaeology) database (e.g., Suda et al 2008, Suda et al 2011, Yamada et al 2013in particular [Eu/Fe] abundance observations are mainly from e.g., Francois et al 2007, Simmerer et al 2004, Barklem et al 2005, Ren et al 2012, Roederer et al 2010, Roederer et al 2014a, Roederer et al 2014b, Roederer et al 2014c, Shetrone, Côté, Stetson 2001, Shetrone et al 2003, Geisler et al 2005, Cohen & Huang 2009, Letarte et al 2010, Starkenburg et al 2013, McWilliam et al 2003. From the raw data, we excluded carbon enriched metal poor stars ("CEMPs") and stars with binary nature, since the surface abundances of such objects are expected to be affected by internal pollution from deeper layers or pollution from the binary companion.…”
Section: Observed Stellar Abundancesmentioning
confidence: 99%
“…They are given in Table 2. The σ EQW errors listed in Table 7 are defined in the same way as in Tafelmeyer et al (2010) and Starkenburg et al (2013). The average abundance error due to the EQW error alone for one average line is σ EQW .…”
Section: Errorsmentioning
confidence: 99%
“…These error bars add in quadrature the random and systematic uncertainties listed in Tables 2 and 5. The sample of Tafelmeyer et al (2010) is shown by upright triangles, while the Starkenburg et al (2013) stars, which were not re−observed at high resolution, are shown by inverted triangles. The sample of Simon et al (2015) including the Frebel et al (2010a) star are indicated by a star.…”
Section: Comparison Samples: References Symbols and Colour Codes Inmentioning
confidence: 99%